The Syrian public's reliance on Russian channels as a source of information in covering military operations in Ukraine - Russia Today channel as a model. (Damascus University Journal of arts and humanities sciences, 2024)
The study aimed to investigate the degree of the Syrian public's dependence on the Russian media as a main source for news information related to the war declared by Russia on Ukraine through the adoption of the Russia Today Arabic channel as a representative model for the Russian Arabic-speaking media.The researcher adopted the descriptive analytical approach, and the assumptions and premises of the theory of dependence on the media to prepare a questionnaire addressed to the Syrian public. The questionnaire consisted of (25) phrases, while the study sample consisted of (249) individuals who were chosen randomly.The study concluded that the Syrian public relies on the Russian media to a high degree to convey news of military operations in Ukraine, and that there are differences in the degree of dependence due to the variable of sex and infavor of the male sample members, and there are differences due to the age variable in favor of the younger age groups.
Keywords: Russian Channels; Russia Today; Military Operations in Ukraine